The Role of Peer Support Providers in Inter-Professional Mental Health Care Teams - Asad, Sarah (Université d'Ottawa / University of Ottawa, 2015)
This qualitative study explores construction of peer support providers’ roles within inter-professional mental health care teams. The study focuses on factors influencing peer support providers' integration; implications of such integration to stakeholders; and views on introducing peer support certification. Interviews were conducted with peer support providers in two formal models of peer support employment in health care organizations in Ontario. Grounded theory approach was used to analyze data. The findings point to a variety of factors that enable peer support providers' integration as well as the challenges that they face in role construction. Implications of role integration suggested multiple benefits to various stakeholders. Participants were generally supportive of certification, but called for more research on this subject. Findings may be transferable to other formal peer models given similar contexts. Understanding of role construction and factors influencing integration may benefit peer support providers and health care organizations about to integrate the role.